Buddhist religious counsellors and the development of competencies for Buddhist sunday school teachers in south Lampung regency - Sri Wartini; Sidartha Adi Gautama; Sandjaja Dharmatanna (Universitas Sebelas Maret, 2025)
This study aims to determine the influence of Buddhist Religious Counsellors in developing the competence of Buddhist Sunday School teachers in South Lampung Regency. The background of this study is based on the low level of competence of BSS teachers, which covers four main aspects, namely pedagogical, personality, social, and professional competence. These suboptimal competencies have a direct impact on the quality of the teaching and learning process and on students' understanding of Buddhist teachings. One of the factors contributing to the low level of teacher competency is the limited number of Buddhist religious instructors, the lack of ongoing training, and the lack of supervision or guidance in teaching practice in the field. This study used a quantitative approach with a simple linear regression analysis method to test the influence between the role of instructors and teacher competency. Data was collected through a closed questionnaire administered to 35 Buddhist Sunday Scool teachers from 11 temples spread across the South Lampung Regency. The results showed that there was a positive influence between the role of Buddhist instructors and the development of Buddhist Sunday School teacher competency. This is evidenced by an R² value of 0.40, which indicates that the role of counsellors contributes significantly to improving teacher competency. Based on these findings, this study recommends optimising the role of Buddhist counsellors through continuous coaching programmes, professional training, and cooperation between counsellors, teachers, and Buddhist religious education institutions. In addition, support from government agencies and religious organisations is essential to improve the quality of human resources in Buddhist education. Thus, the learning process in Buddhist Sunday Schools is expected to be more effective, contextual, and meaningful in accordance with Buddhist values, as well as capable of shaping students' characters in a holistic and balanced manner.